ESTIMASI KANDUNGAN KARBON BIOMASA PNEUMATOFOR Avicennia marina - Gilbert Kindangen; Calvyn Sondak; Deisli R H Kumampung (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Mangrove forests play an important role in mitigating the effects of global warming as mangroves can absorbs and stores carbon therefor, mangrove plants including A. marina can act as carbon sinks. The study aim is to estimate the carbon content contained in A. marina pneumatophore biomass. The data was taken b using line transect method. The number of research stations are 3 stations contain 3 plots (10 x 10 m2) for each station. Samples were taken at low tide by established 3 microplots (50 x 50 cm2) in each 10 x10 m2 plots. The results showed that the highest biomass value was found at Station 3 of 0.49 Kg/m2, followed by Station 1 of 0.42 Kg/m2, and the least pneumatophore biomass value was found at Station 2 of 0.41 Kg/m2. Â This finding is in line to the potenntial potential carbon content in pneumatophores where Station 3 has C content (0.08 Kg C/m2), dand 0.07 Kg C/m2 for both station 1 and 2 respectively. The average of C Contain in pneumatphores was 0.28 Kg C/m2.Â Keyword : Carbon Content, Biomass, Pneumatophores, Avicennia marina